The Effects of Vitamin D Deficiency on Physical Fitness and Sport Performance – A Review - Hoxha, Irida Ikonomi; Bozo, Silvi; Krasniqi, Marsida; Bozo, Dr. Dhurata (South Eastern European Journal of Public Health, 2024)
Introduction: Deficiency or insufficiency of vitamin D affects all individuals, of both sexes and all ages, and consequently brings a series of negative health consequences for them. This deficiency seems to be a very widespread problem in the population in general and also among physically active individuals and particulary in athletes. Currently, the insufficiency of vitamin D is a problem appearing worldwide. While in the population the main source of deficiencies are insufficient exposure to the sun and deficiency in the food diet, in individuals who participate in physical activity and sports it seems that the main factors are high use and depletion of reserves from muscle and adipose tissue. Vitamin D deficiency has an important role not only in bone and muscle health, but also negatively affects physical fitness and sports performance. Therefore, continuing measurement and monitoring of free vitamin D and/or its bioavailable 25(OH)D metabolites is the best way to determine the true vitamin D status for preventive reasons or supplementation in all individuals. Objectives: This review aims to highlight the current situation of the status of vitamin D, especially in subjects participate in physical activity and sports, and its importance and role in the health of athletes and in sports performance. Methods: For this review, we used the database in Scopus and PubMed, searching with key words: vitamin D deficiency - vitamin D status - elite athletes - sports performance. Full articles in English, published from 2016 to 2024, that evidenced the association between vitamin D status and health outcomes and sports performance were included. Results and Conclusions: The results of the study showed that the deficiency of vitamin D in the general population, but also in those who are actively involved in sports and even elite sports, is present at worrying levels. In different groups and populations, the deficiency factors are partly different, but the results show that the lack of food in the diet today constitutes one of the main factors that has almost taken the same weight as insufficient exposure to the sun. For physically active subjects and those involved in various types of sports, deficiencies are present at an unpredictably high rate, putting in serious danger in some cases the lives of the athletes. This comes from a low attention regarding the deficiencies of this vitamin, compared to other elements that are usually taken in the form of supplements in sports. The results show that maintaining an optimal level of vitamin D affects not only the bone and muscle health, the optimal physical fitness of physically active individuals, but also the health and improvement of sports performance (not only physical) of athletes. Therefore, the measurement, monitoring, ensuring a balanced food diet and supplementing with this vitamin, if needed, should accompany the entire course and activity of the subjects of this category in a strict and consistent manner.